Pengaruh Kualitas Layanan, Harga, dan Citra Merek terhadap Keputusan Konsumen dalam Memilih InDrive Sebagai Transportasi Online - Maulana, Muhamad Imam (Jurnal Dimamu, 2025)
Based on the observations, this research is motivated by several issues faced by consumers, such as dishonest drivers and discrepancies between the estimated and actual arrival times provided by the InDrive app. This is despite the fact that InDrive offers various conveniences and benefits to its users.This study aims to determine the impact of service quality, pricing, and brand image on consumer decisions in choosing InDrive as an online transportation service. The object of this research is InDrive users at Ma'soem University. The research employs a quantitative associative approach with primary data, utilizing data collection techniques such as surveys, questionnaires, and literature review. The sampling technique used is nonprobability sampling, specifically purposive sampling. The population consists of faculty members, administrators, and students at Ma'soem University, with a sample size of 101 individuals. The research findings indicate a significant impact of service quality on consumer decisions to choose InDrive as an online transportation service, as evidenced by the t-test results where the t-value (16.600) is greater than the t-table value (1.985). There is also a significant effect of pricing on consumer decisions to choose InDrive, as demonstrated by the t-test results where the t-value (3.446) exceeds the t-table value (1.985). Additionally, brand image significantly influences consumer decisions to choose InDrive, with the t-test results showing the t-value (9.810) surpassing the t-table value (1.985). Furthermore, the simultaneous impact of service quality, pricing, and brand image on consumer decisions to choose InDrive is significant, as indicated by the F-test results where the F-value (155.798) is greater than the F-table value (2.36).